Psychological resilience, athletic experience, and competitive level of judokas. A transversal study - Garrido-Muñoz, M.; Blanco-García, C.; Diez-Vega, I.; García-Merino, S.; Acebes-Sánchez, J.; Rodríguez-Romo, G. (Frontiers in Psychology, 2024)
Introduction: While there is agreement on the positive link between psychological resilience and athletic performance, conclusive findings regarding the association between psychological resilience and other variables of interest (for example, age, gender, type of sport, or competitive level) remain elusive.